Web-based Interactive Visual Media in Teaching Momentum and Impulse to Improve Students' Conceptual Understanding - Pangestuti, Anisa; Amarulloh , Reza Ruhbani; Farizi, Taufiq Al (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2026)
This study aims to develop a visual and interactive learning platform using Google Sites to enhance students’ understanding of momentum and impulse concepts. The research applies a Research & Development with the 4-D model: Define, Design, Develop, and Disseminate. The research instruments included tests, expert validation, and a User Experience Questionnaire, which was completed by students and teachers, covering six dimensions of assessment. The research findings show: (1) The validity scores for the material (94.29%), media (98.3%), and language (96.88%) aspects all fall into the “Highly Feasible” category. These results indicate that the Google Sites–based instructional media is highly feasible for teaching Momentum and Impulse concepts. (2) In terms of practicality, the media achieved scores of attractiveness (2.143), clarity (1.764), efficiency (2.136), accuracy (1.886), stimulation (2.150), and novelty (1.929). These results reflect a highly positive user experience across all aspects measured by the UEQ. (3) The N-Gain test results show a score range of 0.46-0.95 with an average of 0.74 (high category), proving that Google Sites instructional media is quite effective in improving students' conceptual understanding. The use of this instructional media has the potential to contribute to Sustainable Development Goal (SDG) 4: Quality Education by promoting inclusive and equitable learning opportunities. Through the integration of Google Sites, students are encouraged to engage in independent learning, making education more accessible and adaptable to diverse learning needs.